Steganalysis for stegotext based on text redundancy - LUO Gang; SUN Xing-ming (Tongxin xuebao)
Targeted at the text steganography with mimic model,a steganalysis method based on source redundancy for stegotexts was proposed.This method processed the text and the words in it as the m-order Markov source and the source symbols respectively,then computed the redundancy of the source.Through analyzing the relationship between the re-dundancy and the size of the text,the existence of hidden information could be determined.With testing of 8 000 ste-gotexts produced by the four main softwares NiceText,Texto,Stego and Sams Big Play Maker,and 2 400 normal texts randomly sampled from innocuous texts downloaded from the Internet,the results show that the false positive rate of our steganalysis method is 0.5% and the false negative rate is 3.9%.Experiments and analyzing results indicate that the steganalysis method can effectively detect stegotexts based on natural language processing with mimic model.